The effect of particle size and concentration on the ballistic resistance of different shear thickening fluids. (2020) - Grover, Gunjan; Verma, Sanjeev K.; Thakur, Anupama; Biswas, Ipsita; Bhatacharjee, Debarati
Highlights: Effect of particle size and concentration on the rheological parameters of shear thickening fluid (STF). SEM analysis of silica particles. Ballistic trials of STF for the measurement of energy absorption on trial set up. Effect of particle size and concentration on ballistic performance of the STF. Abstract: Shear thickening fluids (STF) have the unique property of increased energy dissipation combined with increased elastic modulus making it ideal for shock absorption applications. The study investigates the effect of particle size and concentration of colloidal silica on the rheological parameters of STF. The particle size of colloidal silica ranged from 100 to 750 nm. Intended for the ballistic performance of STF, the present work also studies the ballistic performance of STF which is a suspension made up of silica of different colloidal particle concentrations in polyethylene glycol (PEG).